Evaluation of a time dependent air pollution model with a new vertical turbulent parameterization - Mangia, Cristina (2000)
The paper presents the evaluation of a model, with a new vertical eddy exchange parameterization, based on a general technique for solving the K-equation, using the truncated Gram-Charlier expansion (type A) of the concentration field and a finite set equations for the corresponding moments. The model can be applied routinely using as input simple ground-level meteorological data acquired by an automatic network. A performance evaluation is shown in the case of continuous emission from an elevated source in a variable boundary layer.